Developing Successful Breeding Programs for New Zealand Aquaculture: A Perspective on Progress and Future Genomic Opportunities - Symonds, Jane E.; Clarke, Shannon M.; King, Nick; Walker, Seumas P.; Blanchard, Brian; Sutherland, David; Roberts, Rodney; Preece, Mark A.; Tate, Mike; Buxton, Peter; Dodds, Ken G. (Frontiers in Genetics, 2019)
Over the past 40 years New Zealand (NZ) aquaculture has grown into a significant primary industry. Tonnage is small on a global scale, but the industry has built an international reputation for the supply of high quality seafood to many overseas markets. Since the early 1990s the industry has recognized the potential gains from selective breeding and the challenge has been to develop programs that can overcome biological obstacles (such as larval rearing and mortality) and operate cost-effectively on a relatively small scale while still providing significant gains in multiple traits of economic value. This paper provides an overview of the current status, and a perspective on genomic technology implementation, for the family-based genetic improvement programs established for the two main species farmed in NZ: Chinook (king) salmon (Oncorhynchus tshawytscha) and Greenshell™ mussel (Perna canaliculus). These programs have provided significant benefit to the industry in which we are now developing genomic resources based on SNP genotyping (genotyping-by-sequencing) to complement the breeding programs, enable evaluation of the genetic health and identify the potential benefits of genomic selection. This represents an opportunity to increase genetic gain and more effectively utilise the potential for within family selection.